Numerical simulation of the damage evolution in the pelvic floor muscles during childbirth. Issue 4 (29th February 2016) - Oliveira, Dulce A.; Parente, Marco P.L.; Calvo, Begoña; Mascarenhas, Teresa; Natal Jorge, Renato M.
Abstract: Several studies have shown that pelvic floor injuries during a vaginal delivery can be considered a significant factor in the development of pelvic floor dysfunction. Such disorders include a group of conditions affecting women like urinary incontinence, pelvic organ prolapse and fecal incontinence. Numerical simulations are valuable tools that are contributing to the clarification of the mechanisms behind pelvic floor disorders. The aim of this work is to propose a mechanical model implemented in the finite element method context to estimate the damage in the pelvic floor muscles by mechanical effects during a vaginal delivery of a fetus in vertex presentation and occipitoanterior position. The constitutive model adopted has already been successfully used in the simulation of childbirth and the structural damage model added has previously been applied to characterize the damage process in biological soft tissues undergoing finite deformations. The constitutive parameters were fit to experimental data available in the literature and the final proposed material model is suitable to estimate the mechanical damage in the pelvic floor muscle during a vaginal delivery. The computational model predicts that even an apparently uneventful vaginal delivery inflicts injuries to the pelvic floor muscles, particularly during the extension of the fetus head, having been obtained more than 10% of damaged fibers. As a clinical evidence, the present work allows to conclude that the puborectalis component of the levator ani muscle is the most prone to damage.